2019
DOI: 10.1177/0309364618791616
|View full text |Cite
|
Sign up to set email alerts
|

UK trial of the Osseointegrated Prosthesis for the Rehabilitation for Amputees

Abstract: This small cohort of patients demonstrates osseointegrated prosthesis allows prolonged usage and improves patients' quality of life compared to conventional prostheses. Clinical relevance These prostheses may provide a future gold standard for amputees and this study provides the first outcome data over such a time period to be reported from outside of the developers group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 25 publications
0
45
1
4
Order By: Relevance
“…A recently published study of persons with a screw-type osseointegration implant revealed also a variability in rehabilitation duration despite a predefined rehabilitation programme. 25 This study contains some limitations. First, the adverse events were extracted from the participants' Radboudumc medical file.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recently published study of persons with a screw-type osseointegration implant revealed also a variability in rehabilitation duration despite a predefined rehabilitation programme. 25 This study contains some limitations. First, the adverse events were extracted from the participants' Radboudumc medical file.…”
Section: Discussionmentioning
confidence: 93%
“…A recently published study of persons with a screw-type osseointegration implant revealed also a variability in rehabilitation duration despite a predefined rehabilitation programme. 25 …”
Section: Discussionmentioning
confidence: 99%
“…9,199 Although serious, adverse events such as periprosthetic or overall fractures, implant loosening, osteomyelitis, revision surgery, or implant removal are rare, they pose a serious clinical concern. 9,10,199 Three long-term follow-up studies (5, >9, and 15 years) indicate that, although improvement in patientreported outcomes has been reported since OI was first introduced, there are still concerns with tissue infection 205,206 and the mechanical properties of the implant, 206,207 possibly related to higher activity. 207 In addition, loss of bone density is associated with implant removal.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…(1)(2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Indeed, surgical procedures are growing at an unprecedented pace worldwide. (18,27,28)…”
Section: Strong Demand For Bone-anchored Prosthesesmentioning
confidence: 99%